INTEGRATED REPORTING DISCLOSURE QUALITY: EVIDENCE FROM EMERGING ASIAN BANKING - Rossa, Prisilla; Lestari, Tri (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Integrated Reporting (IR) integrates financial and non-financial information to enhance accountability and sustainable value creation. In Emerging Asia, however, IR is mostly voluntary, which results in inconsistent and low-quality practices. This study examined the determinants of Integrated Reporting Disclosure Quality (IRDQ) across 76 publicly listed banks in Indonesia, Malaysia, India, China, Vietnam, Thailand, and the Philippines from 2020 to 2023. Using panel data regression, it assessed the effects of ESG disclosure, board independence, leverage, and firm size on IRDQ. The findings revealed that ESG disclosure had a significant positive effect on IRDQ, suggesting that greater ESG transparency enhanced disclosure quality. Conversely, board independence, leverage, and firm size were not significantly associated with IRDQ. Given the voluntary nature of IR in Emerging Asian banking, the results underscore the importance of institutionalizing ESG frameworks. This study provides policy and managerial implications for fostering credible and sustainable reporting in regional banking firms.